Gravity drainage kinetics of papermaking fibrous suspensions - Przybysz, Piotr; Kuncewicz, Czesław; Rieger, František (Polska Akademia Nauk, 2014)
The study analyses application possibilities of filtration and thickening models in evaluation of papermaking suspension drainage rate. The authors proposed their own method to estimate the drainage rate on the basis of an existing Ergun capillary model of liquid flow through a granular material. The proposed model was less sensitive to porosity changes than the Ergun model. An empirical verification proved robustness of the proposed approach. Taking into account discrepancies in the published data concerning how the drainage velocity of papermaking suspension is defined, this study examines which of the commonly applied models matches experimental results the best.
Keywords: drainage; fibrous suspensions; drainage kinetics